PENYESUAIAN ROLE IDENTITY DALAM PERSPEKTIF IMAGINED INTERACTION (Studi Tentang Wanita Yang Ditinggal Mati Suami) - Natakoesoemah, Susilowati (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2015)
The objective of this study is to understand the use of Imagined Interaction as coping to women who lost her husband. Moreover, this study try to understand the self efficacy after the lost of husband and comprehend the psy-chosocial aspects in order to adjust one womens role identity who left by her husband. This study used Honeycutt framework about imagined interaction, and as a supporting study, the author use symbolic interaction concepts. This is a qualitative research that uses post-positivist paradigm method. The data collection method used is in depth interview to 5 women who already lost her husband. Based on this study, identified imagined interaction activities in women who lost husband performed with significant other and devine other. While a role identity adjustment process was found 3 (three) categories are Realistic Adjustment, Moderate Adjustment, and Imagined Adjustment. In the adjustment process there are 3 (three) types of self-efficacy, namely :Acceptance Self-Efficacy: Sincere acceptance towards the lost of husband and optimist about the future; Negotiated Self-Efficacy: Sincere acceptance, however stay pessimist about the future; Imagined Self-Efficacy: Insincere acceptance, lack of confi-dence and very pessimist towards the future.